The sailing of the Intrepid : the incredible wartime voyage of the Navy's iconic aircraft carrier - Williams, Montel; Fisher, David, 1946- (Hanover Square Press, 2025)
From 22-year naval and Marine veteran Montel Williams comes a history of how one World War II aircraft carrier's crew defied all odds, redefining the very meaning of what it means to struggle, persevere and survive.